Fraudulent Financial Reporting Analysis on Non-Financial Companies Listed on IDX in Hexagon Fraud Perspective - Ni Komang Cahyani Purnaningsih; I Gusti Ngurah Agung Suaryana; I Putu Sudana; I Gede Ary Wirajaya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Fraud financial reporting (FFR) is fraud committed by management because of an opportunity, namely the opportunity for management to choose the most profitable accounting method, such as valuation. This study aims to examine the effect of pressure, capability, opportunity, rationalization, arrogance, and collusion on the level of risk of fraudulent financial reporting. The research was conducted on 389 non-financial companies listed on the Indonesia Stock Exchange. The total population in this study was 750 companies. The method of determining the sample used is non-probability with purposive technique. The research method used is quantitative and qualitative research. The data source is secondary data collected through the Indonesia Stock Exchange website. The data analysis technique used in this research is Logistic Regression Analysis. This study states that pressure has no significant and negative effect, capability has a significant positive effect, opportunity has a significantly negative effect, rationalization has a significant positive effect, arrogance has a significant positive effect, and collusion has a significant positive effect on fraudulent financial reporting. The implication of this research is that pressure, capability, opportunity, rationalization, arrogance, and collusion can affect fraudulent financial reporting.